Implementation of the Multy Attribte Utily Theory Method in the Decision Support System for Determining Smart Indonesia Program Assistance (PIP) at SDN 4 Cisalada - Fitry Nur Yani; Mochzen Gito Resmi; Syariful Alam (Institut Pendidikan Indonesia, 2022)
The Smart Indonesia Program (PIP) is one of the government's programs as Poor Student Assistance (BSM). The government program is in the form of cash assistance given to children aged 6-21 years who are still in the world of education. Currently, pip selection at SDN 4 Cisalada from the school is less targeted to have problems in determining potential beneficiaries of assistance where not all students who come from poor families can receive the Smart Indonesia Program (PIP). for this resulting in the injustice of students who should be entitled to PIP funding assistance. To avoid existing problems for the selection of prospective recipients of the Smart Indonesia Program (PIP) requires a Decision Support System (SPK). The Multi Attribute Utility Theory (MAUT) method is a quantitative comparison method that usually combines measurements of different risk and profit costs. Design and Build using the Waterfall method in the process of working on it, the design is made using a flowmap and modeling using Unified Model Language (UML) including Use Case Diagrams, Activity Diagrams, Sequence Diagrams and Class Diagrams. As for programming, it uses PHP and the database uses MySQL. The results of the research that has been carried out by the researcher, it can be concluded by the application of the Decision Support System in determining the determination of PIP assistance in schools using the Multy Attribute Utility Theory (MAUT) method, for the school can be more objective in assessing the determination of PIP recipients, so as to minimize the risk of misuse and distribution of PIP funds to students not appropriately receiving them. Which is in the nature of providing recommendations for decisions to the school.